2011
DOI: 10.4028/www.scientific.net/amr.278.265
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of an Advanced Nickel-Based Superalloy in the as-HIP Form

Abstract: Abstract. This study evaluates the suitability of as-hot isostatically pressed (HIP) RR1000 for noncritical applications in aero-engine components. RR1000, an advanced powder nickel-based superalloy, was developed for disc rotor components in aero-engines. For these critical applications, the consolidated alloy powder particles are extruded to break down carbide and oxide networks, known as prior particle boundaries (PPBs), and to refine the structure into a fine grain size for isothermal forging. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…Comparison of this RR1000 tested under bithemal/TMF conditions with other isothermal crack growth work on RR1000 showed that under isothermal conditions a transgranular fracture was seen for test conditions up to temperatures over 700 o C [16], similar to those seen here. Interestingly, despite the relatively high MATERIALS AT HIGH TEMPERATURES www.materialshightemp.co.uk maximum temperature of the current TMF/bithermal cycle (700 o C) and low test frequency, there was no evidence for intergranular fracture, as reported for Udimet 720Li at test temperatures of 700 o C [14]. This again supports the view that the crack growth seen here under TMF conditions is largely a result of the tensile loads at 400 o C during the thermal cycle, with little contribution from the rest of the cycle.…”
Section: Figurecontrasting
confidence: 48%
See 1 more Smart Citation
“…Comparison of this RR1000 tested under bithemal/TMF conditions with other isothermal crack growth work on RR1000 showed that under isothermal conditions a transgranular fracture was seen for test conditions up to temperatures over 700 o C [16], similar to those seen here. Interestingly, despite the relatively high MATERIALS AT HIGH TEMPERATURES www.materialshightemp.co.uk maximum temperature of the current TMF/bithermal cycle (700 o C) and low test frequency, there was no evidence for intergranular fracture, as reported for Udimet 720Li at test temperatures of 700 o C [14]. This again supports the view that the crack growth seen here under TMF conditions is largely a result of the tensile loads at 400 o C during the thermal cycle, with little contribution from the rest of the cycle.…”
Section: Figurecontrasting
confidence: 48%
“…Although these initial isothermal tests were relatively trivial, the results suggested that this facility could produce acceptable conventional fatigue crack growth data using the same PD measurement system as planned for the TMF testing and there was no impact of using the radiant lamp furnace to provide the required temperature. It is worth noting at this point that the test piece design and general test approach has been used extensively for isothermal fatigue crack growth testing for many years [9,13,14]. Thus the crack length and PD measurement have been fully calibrated and demonstrated for isothermal testing, using this same test piece design.…”
Section: Crack Growth Rate Measurements and Facility Demonstrationmentioning
confidence: 99%
“…PPB networks tend to form on these larger less-deformed powder particles. However May et al [33] found that a greater degree of PPB decoration occurs in the finer powder particle size fraction, and following a super-solvus heat treatment these PPBs pin grain boundaries of the fine powder particle, while the reduction of PPB decoration in coarse powder particle compacts allows significant grain growth.…”
Section: Powder During Hiping Processmentioning
confidence: 99%
“…Since lower strain rates are used during deformation, isothermal forging at slow strain rates and high temperatures (slightly below the γ' solvus) [43] currently offers greater control on structure and enables quire complexity, nearnet shaped components to be formed [44]. May et al [33] stated that for critical applications such as disc rotor components in aero-engines, the consolidated alloy powder particles should be extruded to break down carbide and oxide networks, i. e. PPBs, and to refine the grain size for isothermal forging. Mourer et al [45] produced a billet of René 104 with a diameter of 235 mm, from which to manufacture a military aircraft engine high pressure turbine disk with dual microstructures.…”
Section: Effect Of Deformation On Ppbsmentioning
confidence: 99%
“…Excellent fatigue performance, damage tolerance, and good creep resistance at operation temperatures close to 750 • C [1][2][3] originate principally from the presence of high volume fraction (close to 50%) of gamma-prime (γ ) precipitates coherently embedded within the gamma (γ ) matrix [4,5]. The optimisation of the precipitate size distributions (PSDs) for these properties involves careful control of cooling conditions.…”
Section: Introductionmentioning
confidence: 99%